Our Fight Has Just Begun Hate Crimes and Justice in Native America - Bennett, Cheryl Redhorse, 1978- (Book collections on Project MUSE., 2022)
"This book provides a compelling history, documentation and analysis of hate crimes committed against Navajos and Native Americans in the Four Corners"--